Two chronically misdiagnosed patients infected with Nocardia cyriacigeorgica accurately diagnosed by whole genome resequencing - Liu, Anqing; Liu, Xiaojin; Lu, Yunwei; Gao, Zhan; Tang, Ruixiang; Huang, Yang; Zheng, Liheng; Fan, Zhenxin; He, Miao (Frontiers in Cellular and Infection Microbiology, 2022)
Nocardiosis is a rare but life-threatening infection particularly affecting immuno-compromised hosts, causing localized or systemic suppurative disease usually in human beings. Nocardia species, as the pathogen of nocardiosis, are difficult to differentiate because of their complex colony morphological features. In this study, we describe two patients who had been misdiagnosed for a long time infected with Nocardia cyriacigeorgica with completely different morphology were accurately diagnosed. Single colonies were analyzed by Gram staining, acid-fast stain, mass spectrometry and whole genome resequencing (WGRS). These two bacterial, strains L5.53 and L5.54, were found to be Gram-negative and acid-fast-weak positive. Blood sample culturing of strain L5.53 yielded white colonies, which were like a layer of hoarfrost, while colonies of L5.54 were yellow, rough, slightly convex. The two strains were identified as Nocardia sp. by mass spectrometry, and WGRS accurately determined them as N. cyriacigeorgica. After medical treatment, one patient was cured and the other was still receiving treatment in the hospital. It can be seen that Nocardia sp. cannot be accurately classified and identified only by phenotypic tests such as bacterial morphological differences, so it is necessary to identify Nocardia spp. with phenotypic tests in combination with other molecular biology technologies, such as WGRS.